Evaluation of haemoglobin in blister fluid as an indicator of paediatric burn wound depth. Issue 5 (August 2015) - Tanzer, Catherine; Sampson, Dayle L.; Broadbent, James A.; Cuttle, Leila; Kempf, Margit; Kimble, Roy M.; Upton, Zee; Parker, Tony J.
Highlights We measured free haemoglobin abundance in paediatric burn blister fluid. Haemoglobin was associated with burn depth and time from injury to presentation. Haemoglobin abundance was also related to time to reepithelialisation. The consequences of free haemoglobin in burn wound environments remains unclear.